Tea Tree Oil and Terpinen-4-Ol Induce Cytoskeletal Reorganization of Human Melanoma Cells - Bozzuto, Giuseppina; Mariano, Fulvia; Costa, Ilaria; Calcabrini, Annarica; Molinari, Agnese (Planta Medica International Open, 2022)
Tea tree oil is an essential oil distilled from the leaves of Melaleuca alternifolia, a plant native to Australia. It has been used in traditional medicine for its antiseptic and anti-inflammatory properties to treat various skin conditions and infections. It has also been incorporated into many topical formulations to treat cutaneous infections and speed wound healing. In vivo and in vitro studies report antiproliferative effects in skin disorders but the molecular mechanisms underlying this effect remain to be still elucidated. In this study MTT assay, scanning electron microscopy-field emission gun, flow cytometry, cell cycle assays, and laser scanning confocal microscopy were utilized to investigate a novel mechanism underlying the antiproliferative effects of tea tree oil and terpinen-4-ol on transformed skin (melanoma) M14 cells. The analysis of the actin cytoskeleton by laser scanning confocal microscopy evidenced a clear action of both essential oil and its main active component on F-actin, which interfered with bundling of actin microfilaments in stress fibers. As for the microtubular network, both tea tree oil and terpinen-4-ol induced a disorganization of the perinuclear cage with the rupture and collapse of microtubules. Finally, they noticeably changed the intermediate filaments architecture by inducing the formation of large vimentin cables. Results obtained in the present study point to the cytoskeleton as a further target of tea tree oil and terpinen-4-ol and could account for the inhibition of proliferation and invasion of skin transformed M14 cells. In our experimental conditions, vimentin intermediate filaments appear to be the cytoskeletal element more affected by the treatments. Moreover, the role of cross-linker proteins in the mechanism of action of tea tree oil has been discussed.
Keywords: Melaleuca alternifolia; Myrtaceae; tea tree oil; terpinen-4-ol; cytoskeleton; melanoma